2021
DOI: 10.7202/1076756ar
|View full text |Cite
|
Sign up to set email alerts
|

A Life-Transformative Education for the 21st Century: Exploring, Creating, and Leading Through Honors

Abstract: This article explores the theoretical underpinnings of life-transformative education and gifted education and applies them to a university honors program. Life-transformative education requires authentic learning experiences and rich mentorship relationships to promote happiness, well-being, and a sense of purpose. This is intended for all students, so the literature on gifted education is used to differentiate an honors education. Several competing paradigms exist, and the University of Connecticut Honors Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The integration of technology is vital for preparing students for a technology-driven future (Abitoye et al, 2023), and the reported 60% involvement is promising. Critical thinking, a cornerstone of transformative education (Chancey & Lease, 2020), appears to be actively encouraged, as evidenced by the high participation rate. These findings suggest that while transformative practices are not universally prevalent, there is a significant foundation and receptivity for such approaches within the education system.…”
Section: Resultsmentioning
confidence: 99%
“…The integration of technology is vital for preparing students for a technology-driven future (Abitoye et al, 2023), and the reported 60% involvement is promising. Critical thinking, a cornerstone of transformative education (Chancey & Lease, 2020), appears to be actively encouraged, as evidenced by the high participation rate. These findings suggest that while transformative practices are not universally prevalent, there is a significant foundation and receptivity for such approaches within the education system.…”
Section: Resultsmentioning
confidence: 99%
“…Many honors educators aspire to develop the skills of collaborative, interdisciplinary leadership among their students, often citing these as the learning outcomes of their programs (Chancey et al, 2019). The work of our Collaborative not only led to the development of such a transformative learning experience for students, but also our modelling of the same skills for students at our institutions.…”
Section: Modeling the Promise Of Honors Educationmentioning
confidence: 99%
“…In order to optimize the implementation of the prototype curriculum at MAN 2 Tanjung Jabung Barat, cooperation from various parties is needed, mainly the role of the head of the madrasah himself as the leader. One of the factors causing quality or non-quality education is determined by the competence and leadership of leaders in managing education (Chancey & Butts, 2020;Cruz-Gonzalez, 2021). If a leader cannot manage, influence, or invite his members to achieve educational goals, is unable to take advantage of existing opportunities, and tends to apply a leadership style that merely carries out routine tasks, then it is not expected that the quality of education will increase (Hayes et al, 2021;Hoque et al, 2023).…”
Section: Introductionmentioning
confidence: 99%